(Regs-)beginsels en (regs-)norme: Enkele kritiese opmerkings - Raath, A. G. W. (Koers, 1984)
This is an inquiry into the meaning of and relationship between jural principles and jural norms. The theories of both H. Dooyeweerd and H.G. Stoker are subjected to a critical analysis. It is concluded that in so far as Stoker's theory of legal principles is brought into relationship with the divine calling of man in cosmic reality and his theory of jural norms into relationship with the manner in which man ought to answer to this calling and fulfill his vocation, it opens up important scientific avenues for exploration. Furthermore the differences between Stoker's view and those from the ranks of the “Philosophy of the Cosmonomic Law Idea” are investigated.